The Application of Group Social Guidance in the Development of Drug Convicts in Correctional Institutions - Ulang Mangun Sosiawan (Jurnal Penelitian Hukum De Jure, 2021)
Group social guidance is a method of social work that aims to help individuals to improve their social functions through certain experiences within the group so that they are able to overcome the problems they face, whether problems involving themselves, their group and society. In providing guidance for drug convicts, group social guidance tends to be more effective than individual social guidance. The forms of group social guidance carried out in correctional institutions include general education, skills education, mental spiritual development, socio-cultural and work activities. The problems that were studied are how to apply group social guidance for drug convicts, what the benefits of the guidance are and whether there are obstacles it faces. The method used is empirical normative method. The results of the study concluded that (1) Group social guidance for drug convicts is carried out in collaboration with the Wahana Bhakti Sejahtera Foundation which specifically handles drug convicts and it has been running properly, implemented through spiritual group activities, sports, arts, legal awareness and work guidance. (2) Group social guidance activities show good results, as can be seen from the positive self-changes in drug convicts. (3) The obstacles are the limited infrastructure for development, drug convicts’ laziness in following guidance, the lack of application of values and the lack of active participation of the officers as social workers in conducting guidance. It is recommended to add facilities and infrastructure for medical therapy and social rehabilitation for convicts who are ex-drug users.